Floating Drug Delivery Systems Using Metronidazole as a Model Drug Part I: By Effervescent Method - Abather A K. Sadiq; Rihab A J. Altaii; Fatima A. Tawfiq (College of Pharmacy / Mustansiriyah University, 2013)
Gastric retentive dosage forms are highly useful for the delivery of many kinds of drugs. The use of floating dosage forms (FDFs) is one of the methods used to achieve prolonged gastric residence time (GRT). Formulation of Metronidazole (MDZ) as FDF provides an opportunity for both local and systemic drug action for eradication of Helicobacter pylori which is a gram-negative bacterium that is associated with gastric inflammation, peptic ulcer, and gastric cancer. This study was undertaken in order to formulate effervescent single-unit floating drug delivery system (FDDS) for MDZ. In the effervescent method, a carbon dioxide generating agent, e.g. sodium bicarbonate, was incorporated in hydrophilic polymer matrix together with MDZ. Different formulation parameters were studied and their effects on the floatation and in vitro drug release profiles were investigated. Polyvinyl pyrrolidone (PVP) provided rapid hydration of matrix, and this influence was decreased with time. Pectin was found to meet the requirements needed from a matrix for drug delivery applications including suitable mechanical properties to confine the gas, and to sustain MDZ release. The optimal amount of polymer and effervescent agent, lubricant agent concentration, and compression force were also demonstrated. The stability of the selected floating MDZ tablet formula (6) was also studied at different temperatures for three months and the calculated expiration date was found to be more than 4 years